SPT-T: test procedure and applications - Peixoto, A. S. P.; de Carvalho, D.; Giacheti, H. L. (Millpress Science Publishers, 2004)
Ranzini (1988) proposed the Standard Penetration Test with torque measurement (SPT-T) and some geotechnical engineers in Brazil have been using it since 1991. This paper presents the state of the art on SPT-T testing, emphasizing what is already established as common knowledge in Brazilian engineering practice, besides a suggestion for test procedure, including equipment and practical aspects. In addition, the study of the shape of the torque versus rotation-degree angle curve obtained by an electric torquemeter used in several SPT-T tests carried out on six experimental research sites in the southeast region of Brazil is discussed here. Four different methods to predict pile capacity based on SPT-T test results are briefly presented and a comparison with load tests carried out on different types of piles, on those six experimental research sites, is presented.
Keywords: Standard Penetration Test; torque measurements; soil classification; lateral skin friction of piles